Ефективність використання логічного аутсорсингу на польських підприємствах - Жебруцький, З.; Кручек, М. (Видавництво Національного університету "Львівська політехніка", 2009)
Наведено вибрані аспекти аутсорсингу на польських підприємствах. Головну увагу сконцентровано на ефективності використання аутсорсингу, а також представлено в цьому контексті бар'єри і шанси для впровадження аутсорсингу на польських підприємствах. Оцінюється обслуговування клієнта для гірничого підприємства і авторизованих продавців. Досліджено рівень і діапазон контролю наданих послуг і способу комунікації, що концентрувались на пошуку заходів оцінки ефективності аутсорсингу, встановлено, які процеси найчастіше підлягають виділенню. The paper presents selected aspects of logistic outsourcing in polish companies. The main goal was focused on pointing out the efficiency of use of outsourcing services. The article presents also barriers and chances for implementation of outsourcing in polish companies. The case study is an example for evaluation of customer service for coal company and coal sellers. The article presents the second part of researches of authors above the use of autsorsing in the Polish enterprises. A level and range of control of the given services and method of communication is probed in this part, concentrated on the search of measures of estimation of efficiency of autsorsing, it is set, what processes are subject more frequent all a selection. Businessmen specified also on actors, which pretended to be to success and make the factors of success, and also barriers in the grant of autsorsing's services.